THE INFLUENCE OF INTELLECTUAL CAPITAL AND SHARIA COMPLIANCE TO THE BANKING FINANCIAL PERFORMANCE IN INDONESIA - Khoirunnisa Azzahra (Universitas Islam Balitar, 2020)
This study aims to analyze the effect of intellectual capital and Sharia Compliance on Financial Performance. This study also uses several variables that are identified as factors that affect Financial Performance including intellectual capital as measured by using Value Added Intellectual Coefficient (VAIC), and sharia compliance as measured by using Islamic Income Ratio (IsIR) proxy. The research method used is quantitative descriptive by using multiple linear regression test models. Sampling was carried out using a purposive sampling method so that 7 Islamic banks in Indonesia were obtained with 42 researched data used as research samples and hypothesis testing was performed using simultaneous significant tests (F test) and partial significant tests (t test) with ɑ = 5%. F Test results show that intellectual capital, and sharia compliance together have a significant positive effect on financial performance. T test results show that intellectual capital and Sharia Compliance have a significant positive effect on financial performance.